Slope Stability Analysis for Mine Slope Design Optimization Planning at Pit Middle of PT Banjarsari Pribumi Open Pit Mine, Merapi Timur, Lahat, South Sumatera - Dendi Fermon Dika; Yoszi Mingsi Anaperta (Departemen Teknik Pertambangan FT UNP, 2024)
PT Banjarsari Pribumi is a subsidiary of PT Titan Infra Energy (Titan Group) which is engaged in coal mining. The company is located in Merapi Timur, Lahat, South Sumatera. PT Banjarsari Pribumi conducts mining using the Open Pit Mining method. To determine the safety factor using the morgenstren-price method. The results of the slope stability analysis for Section A-A' obtained a saturated FK of 1.092, saturated FK Section B-B' of 1.041 saturated FK Section C-C' of 1.148. From the analysis results obtained, it is explained that the slope is in critical condition. For this reason, the authors conducted a slope dewatering simulation and a resloping + dewatering simulation on the Lowwall Pit Slope. The results of the 2 m dewatering simulation for section A-A' obtained an FK value of 1.454, for dewatering 10 m section B-B' FK value of 1.301 and for dewatering 5 m C-C' FK value of 1.301. The resloping simulation results for section A-A' obtained an FK value of 1.319. The resloping + dewatering simulation results for section B-B' obtained an FK value of 1.345 and for section C-C' of 1.369.